Energy psychology interactive rapid interventions for lasting change : an interactive 40-hour course for mastering the basic concepts and techniques of energy psychology - Feinstein, David; Gallo, Fred P.; Eden, Donna; Innersource (Firm) (Ashland, OR : Innersource, 2004)
Self-study tutorial designed to teach psychotherapists and psychologically-oriented energy healers the basic principles of energy psychology. Features 16 modules with illustrations, tables, charts, links, and practice sessions in a question and answer format
Also issued the textbook 297 pages includes indexes
Psychotherapists and other healthcare professionals
System requirements for Windows: PC; 128MB RAM; Windows 95 or higher; Microsoft Internet Explorer 5.0 or higher; VGA color monitor; CD-ROM drive
System requirements for Macintosh: Macintosh processor; 128MB RAM; MacOS 9 or higher; Microsoft Internet Explorer 5.0 or higher; VGA color monitor; CD-ROM drive
Keywords: Energy psychology; Mind and body therapies; Mental healing